Implementasi Payment Gateway pada Aplikasi Penjualan Beras Berbasis Website Menggunakan Pendekatan Extreme Programming - Rahayu, Sri; Natsir, Dimas Muhamad Fauzy (Institut Teknologi Garut, 2025)
The agricultural sector, including rice production, plays an important role in the Indonesian economy. PD. PJ, a rice trading company in Garut Regency, West Java, faces challenges in providing product information access and cash transaction security in large-scale sales. This research aims to implement payment gateway technology in a web-based rice sales application, using the Extreme Programming approach, because conventional payment methods such as manual transfers and cash payments often cause delays in confirmation, risk of errors, and difficulties in the transaction verification process. The stages used include planning, design, coding, and testing. The results showed that this application is able to optimize sales services, based on Blackbox testing on 24 test classes and Beta System Usability Scale testing which reached a score of 80.29, indicating that the application is in the acceptable category.